Analisis Net Profit Margin dalam Meningkatkan Pertumbuhan Laba pada Depo Air BWR Genggong - Rahmanda, Muhammad Rizki; Muzakki, Ahmad; Billah, Zahida I’tisoma (MES Bogor, 2024)
This study aims to analyze the relationship between Net Profit Margin (NPM) and profit growth at Depo Air Minum BWR Genggong, using a quantitative research method with a descriptive approach. Historical data on net profit, revenue, and years were obtained from the company's financial statements. The descriptive analysis results show NPM fluctuating between 49.71% and 65.06% during the period, while profit growth varied, including both positive growth and decline. Hypothesis testing indicates a significant relationship between NPM and profit growth, with a p-value smaller than the significance level. Additionally, the correlation between NPM and profit growth is 0.78, indicating a strong relationship. These findings confirm that increasing NPM could potentially boost profit growth, highlighting the importance of operational efficiency and financial management in influencing a company's financial performance. In conclusion, this study provides insights into the factors affecting financial performance and their implications for future business strategies.